ANALISIS KELAYAKAN INDUSTRI TAHU DI DESA KANCINAA KECAMATAN PASARWAJO KABUPATEN BUTON (STUDI KASUS PADA IKM DWI BERKAH) - Edy, Safrin (Media Agribisnis, 2019)
The aim of this research was: (1) to find out the amount of income received from the tofu business; (2) to find out the value of the viability of the tofu business. This research was carried out in the IKM Dwi Berkah industry in Kancinaa Village, Pasarwajo Sub-district, Buton Regency from July to August 2019, considering that the Kancinaa Village was one of the areas of tofu business and that the area was easily reached. This type of research is a case study, so that tofu-making business owners are used as a source to gather the information needed by researchers. The data obtained were then analyzed using a profit analysis of ?= TR-TC and researchers used the R / C ratio formula to determine the feasibility of the business. The results of this research show that the profit is Rp 58,094,450/month in a single production process. In addition, the 1.51 R / C ratio was also achieved in such a way that the IKM Dwi Berkah tofu industry was competitive and viable to grow in the Kancinaa Village Pasarwajo Sub-district of Buton Regency.   Keywords: feasibility, efficiency, cost, tofu industry